José Julio Martín Romero, La guerra en la literatura castellanadel siglo XV, Londres, Department of Iberian and Latin American Studies... - Sergio Moreno Jiménez (Tirant)
José Julio Martín Romero, La guerra en la literatura castellanadel siglo XV, Londres, Department of Iberian and Latin American Studies, Queen Mary, University of London (‘Papers of the Medieval Hispanic Research Seminar’, 23), 2015, 121 pp.